Tinjauan Hukum Terhadap Pengelolaan Sampah Daerah - Agostinho G.L.S. Fernandes (Hikamatzu | Journal of Multidisciplinary, 2026)
Waste management problems are one of the environmental issues that continue to increase in Indonesia due to population growth, urbanization, industrial development, and changes in community consumption patterns. Poorly managed waste can cause various negative impacts, such as environmental pollution, public health problems, flooding, and ecosystem damage. Therefore, waste management requires clear legal regulations and effective as well as sustainable policy implementation. This study aims to analyze the legal regulations of regional waste management, the implementation of law in waste management, and the obstacles faced in its implementation. This research uses a normative legal research method with statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed descriptively and qualitatively. The results show that waste management in Indonesia already has a strong legal basis through Law Number 18 of 2008 concerning Waste Management and Law Number 32 of 2009 concerning Environmental Protection and Management. The implementation of waste management is carried out through the provision of facilities and infrastructure, waste bank programs, and policies to reduce the use of single-use plastics. However, its implementation still faces several obstacles, such as low public awareness, limited facilities and infrastructure, weak law enforcement, and lack of coordination among institutions. Therefore, it is necessary to strengthen regulations, improve public education, enforce stricter laws, and enhance cooperation between the government, society, and the private sector so that regional waste management can be carried out effectively and sustainably